Biopigments (Phycoerythrin, Fucoxanthin and Siphonaxanthin) from Seaweeds and Their Potential Applications as Ingredients in Cosmeceutical Industries: A Review. Issue 1 (1st December 2022) - Noviendri, D; Hasrini, R F; Subaryono,; Marraskuranto, E
Abstract: Green seaweed, red seaweed, and brown seaweed are the three main kinds of seaweeds, which are also categorized as macroalgae. The color represents chemical compounds known as photosynthetic pigments (biopigments) including carotenoids, chlorophylls, and phycobiliproteins. This review is focused on three biopigments, such as phycoerythrin (PE), fucoxanthin (FX), siphonaxanthin (SX), and their potential application as ingredients in cosmeceuticals industries. PE is a form of a marine bioactive protein called phycobiliprotein, which is primarily present in red seaweed, such as Halymenia sp., Euchema sp., Gelidium pusillum, Gracilaria verrucose, etc. The main xanthophyll carotenoid found in brown seaweed, such as Padina australis, Sargassum horneri, Undaria pinnativida, etc., is FX. Following that, SX is a rare xanthophyll carotenoid that is prevalent in green seaweed, including Codium fragile, Halimeda sp., etc. An epoxide and a bond of allenic are both present in the structure of FX, whereas these moieties are absent in the SPX structure. Generally, there are two main techniques to extract these biopigments: the conventional method (liquid solvent extraction), and the non-conventional. Furthermore, due to their antioxidant, antiaging, anti-inflammatory, anti-tyrosinase, etc. activities, PE, FX, and SX demonstrated strong potential as cosmetic activities. These biopigments are being explored as possible components for cutting-edge cosmeceuticals. There is still a need for additional research to assess the safety, effectiveness, and actual possible alternatives of using biopigments from seaweeds in the cosmeceutical business, despite the challenges of developing environmentally safer extraction techniques.